Face - Fernández Ocampo, Victor Alfonso (Cinzontle, 2025)
Viktor FernandezHe was born on July 18, 1985 in La Unión, Valle del Cauca, Colombia. He began painting, attending the workshop of master Jairo Rosas, at the age of 14; place where he ventured and obtained his first art samples, at the age of 17. After there, in 2022 he began his professional studies in plastic arts at the Departmental Institute of Fine Arts in the city of Cali, Colombia, where he currently continues his studies. His works are classified into three main themes; which are: bullfighting, landscape and kinetic. Throughout his career he has participated in several national and international exhibitions such as: La Cometa Gallery Auction, Bogotá, Colombia, 2006; La Unión Valle Mayor's Office, La Unión, Valle del Cauca, Colombia, 2017; Inside the color, Cali, Colombia, 2019; Bullfighting Expo, Manizales, Colombia, 2018; Colombia Tierra Querida, Miami, USA, 2022; Arte Anima Latina, Perugia, Italy, 2024; among others.